Case Report: A severe case of traumatic ankle fracture-dislocation with medial malleolar bony defect and 5-year follow-up - Hung, Wei-Cheng; Chang, Chien-Chun; Kuo, Chien-Chung (Frontiers in Surgery, 2025)
Open fracture-dislocations with significant malleolar bone and soft tissue loss, along with ligament injuries, are complex and often require extensive treatment and staged surgeries. The aim of this report is to highlight treatment strategies and key considerations, including surgical reconstruction with allografts or autografts and various flap techniques as viable options. Additionally, deltoid ligament repair or reconstruction is crucial for surgical success. We report the case of a 29-year-old woman with no significant medical history who sustained an open fracture-dislocation of the left medial malleolus and midfoot due to a lifeboat propeller injury while white water rafting. The injury led to substantial bone and soft tissue loss and deltoid ligament injury. Following multiple wound debridements, the ankle was successfully reconstructed using an AO distal tibia plate, autogenous iliac bone graft, tension band wire, cancellous screw, and free anterolateral thigh flap, with direct deltoid ligament repair. The patient was followed up for 5 years, with favorable outcomes.